BOAS in the Boston Terrier: A healthier screw-tailed breed? - Francesca Tomlinson; Ella O'Neill; Nai-Chieh Liu; David R Sargan; Jane F Ladlow (PLoS ONE)
Brachycephalic obstructive airway syndrome (BOAS) is well documented in the three most popular brachycephalic dog breeds of the UK and several other countries: French Bulldogs, Pugs and Bulldogs. More extreme conformation has been found to be associated with increased risk of BOAS and other brachycephalic disease in these breeds, such as ocular, neurological, and dental disease. Less is known about how BOAS and other brachycephalic conformation-related disease affects other breeds such as the Boston Terrier. In this study, one-hundred and seven Boston Terriers were prospectively recruited from the UK dog population and underwent clinical assessment, respiratory function grading and conformational measurements. Whole-body barometric plethysmography was used in a smaller cohort of dogs to compare the quantitative differences in respiratory parameters between both affected and unaffected Boston Terriers, and control mesocephalic dogs. When compared to an equivalent study population of French Bulldogs and Bulldogs, it was found that Boston Terriers have a significantly higher proportion of BOAS Grade 0 dogs at 37.5% compared to 10% and 15.2% respectively (p<0.01). Within the breed, more extreme brachycephalic conformation was found to be associated with an increased risk of BOAS: specifically, nostril stenosis, facial foreshortening, abnormal scleral show, and higher neck to chest girth ratio. However, there is considerable overlap between measurements of affected and unaffected dogs in these variables. Therefore, the use of respiratory function grading is likely to be more advantageous for owners, breeders, and veterinary surgeons in accurately selecting unaffected dogs.